Guest

Tell me answer step by step. Please sir how it can be solve. I do not know please help me.

Tell me answer step by step. Please sir how it can be solve. I do not know please help me.

Question Image
Grade:12th pass

1 Answers

Nandana
110 Points
4 years ago
hi !
      √(1+cos2x) = √(1+cos2 x -sin2 x)
                          =√(cos2 x + x2sin+cos2 x - x2sin)
                          =√(2cos2 x)
     now,
           √2 ∫sinx cosx dx
                u = sinx
              du = cosx dx
              =  √2 ∫ u du
              =  1/√2 sin2 x + K  
                 where , K is orbitary constant
  

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free